Kontradiksi dalam Asumsi Religiusitas pada Bangsa Jepang: Telaah Filosofis Pergeseran Makna Religi - Sartini, Sartini (Jurnal Filsafat "WISDOM", 2003)
The religion generally creates religious society. The religious society principally could be seen from their attitude that follow religious norms, becouse religion it self guides the people not to do something bad. But in special case, religious Japanese people were founded something unusual and contradict to this ideal values. In the history, the concepts of Geisha, Jugan lanfu, and any sexual harassments had been founded in religious Japanese people. This contradiction may be caused by the change of their religion point of view.